If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x = x + 5 + 2x + -1 Reorder the terms: 4x = 5 + -1 + x + 2x Combine like terms: 5 + -1 = 4 4x = 4 + x + 2x Combine like terms: x + 2x = 3x 4x = 4 + 3x Solving 4x = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4x + -3x = 4 + 3x + -3x Combine like terms: 4x + -3x = 1x 1x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 1x = 4 + 0 1x = 4 Divide each side by '1'. x = 4 Simplifying x = 4
| 4(j+5)=2 | | 13-2=j+6 | | -4(4a-8)= | | -4(4a-7)= | | Y=-12e^2x+36e^4x | | r+0.48=1.6 | | h(t)=-16x^2+85 | | 6(1)-(-7)=13 | | c/3+7=11/2 | | -(1+11n)= | | 6x+3x=1251 | | 5x+11=35 | | 2h+3.4forh=3 | | 5x-3=21-X | | x/2+2/7= | | -4-6m-m=2m-4 | | Y=7(x+870) | | 24x+4(x-2)=10(x+2)+8 | | -4(b-3)= | | 1.50h+9.99=36.99 | | Y+24=-14 | | 10+22xn=98 | | 18-4n=6-16m | | 2(4(5)-12)+3(5)= | | 6+x+3=4x+8 | | b+11/17= | | 0=(5x-2)(x+7) | | (2x+4)+X=10 | | -7(7-6k)= | | 60=4(x-2)+5(8x-4) | | 15w-12=3 | | r^2-5r-6=0 |